Development of an Arsenobetaine Standard Solution with Metrological Traceability to the SI by an Arsenic‐specific Mass Balance Method. (25th January 2017) - Ko, Kyung‐Moon; Kim, In Jung; Go, Cheongah; Yim, Yong‐Hyeon; Lim, Yongran; Kim, Tae Kyu; Yoon, Ilsun; Hwang, Euijin; Lee, Kyoung‐Seok
Abstract : An arsenobetaine (AsB) standard solution with metrological traceability to the International System of Units was developed as a calibration standard for the quantitative analysis of AsB. An arsenic‐specific mass balance method was established for the certification of the AsB standard solution. The accurate mass fraction of total arsenic in the solution was determined by instrumental neutron activation analysis with direct comparator method. Arsenic‐containing impurities were evaluated by arsenic speciation analysis using liquid chromatography‐inductively coupled plasma mass spectrometry (LC‐ICP‐MS). Two LC separation methods were adopted for comprehensive coverage of the impurities, which include the reversed‐phase LC with ion‐pairing and the cation exchange chromatography. The only arsenic‐containing impurity observed by LC‐ICP‐MS was trace level of trimethylarsine oxide. The mass fraction of arsenic in the form of AsB was obtained by subtracting the arsenic mass fractions of the impurities from the total arsenic in the standard solution. The between‐bottle inhomogeneity of AsB content in the standard solution was less than 0.7%, which was estimated from the relative standard deviation of the measurement results obtained from 10 representative sample bottles from a batch. The certified value of AsB and its expanded uncertainty as arsenic mass fraction were assigned to be (51.28 ± 1.17) mg/kg ( k  = 2 approximately at 95% level of confidence). Abstract :